Prosedur Penyelesaian Sengketa dalam Perbankan Syariah: Tinjauan Terhadap Kasus di Pengadilan Agama Tasikmalaya - Eman Suherman; Ramdhani Wahyu Sururie; Oyo Sunaryo (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
Dispute resolution in sharia banking involves various methods, such as mediation, arbitration and court. Mediation is a voluntary process that allows the parties involved to reach an agreement with the help of a mediator. Arbitration is a method that results in a binding decision by a neutral arbitrator. Trial is a formal method that requires a longer process and higher costs, but produces binding decisions. Each method has advantages and disadvantages, and the choice of method must consider the characteristics of the dispute, the preferences of the parties involved, and compliance with sharia principles in Islamic banking. In conclusion, it is important to choose the dispute resolution method that best suits the Islamic banking context and the desired resolution objectives.